Vehicles - Piroddi, Chiara 1982-; Baruzzi, Agnese; Iceigeo (Firm) (Milan, Italy White Star s.r.l., 2022)
"Planes, boats, cars, and bikes--there are so many modes of transportation to choose from! Babies can observe the black and white images, discover little details in red, and start exploring the world" --
On board pages.
Cover title.
Chiefly illustrations.
Only book cover has text.
For 0-12 months.
111285
Keywords: Vehicles -- Juvenile literature; Shapes -- Juvenile literature; Board books; Wordless picture books